Clinical and histopathological pattern of colorectal malignancies, the experience in a tertiary hospital in south-western region, Saudi Arabia - Aldayhum, Majed Saleh M.; R. Alshehri, Anas Abdullah; AlQahtani, Dlaim H.; Alfussaily, Eman Yahia; Althibait, Suha Abdulrahman S.; Alshehri, Ziyad Abdullah R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Colorectal cancer is the third most common cancer all over the world and the second leading cause of the cancer death in both sexes. CRC is the second most common cancer in Kingdom Saudi Arabia. However, this aspect was not recently studied. Methods: This is a retrospectively cohort based study. We collected and analyzed the records of the patients with CRC diagnosed at Aseer Central Hospital, Abha, Saudi Arabia from January 2008 to June 2016. A pre-specified data sheet was used to collect information regarding socio-demographics, age, Altitude, site of tumor, clinical presentation, outcome and prognosis as well as histopathological pattern of cancer and the stages of disease. Descriptive statistics was performed using SPSS. Results: A total of 291 cases of CRC were registered in the Aseer Central Hospital. 171 cases 58.87% were males while 120 cases 41.2% were females. The mean age of patients (SD) at the time of diagnosis was 59.38 years. At the time of diagnosis, 219 patients 84.6% presented with early stage disease and 40 15.4% had distant metastasis advanced stage. The most frequent CRC located in sigmoid 26.5%, rectal 23.7%and 14% in ascending. The moderately differentiate adenocarcinoma grade of tumor is being the most common grade among all variants 75.6%. Conclusions: In this study, we have nearly similar results found in previously published study by Alshehri et al. Males considered most affected, most of the patients were more than 50 years, 84.6% of the patients came with early stage disease. Left side colon were the most common site of CRC.